Dietary Supplementation with Phytase and Protease Improves Growth Performance, Serum Metabolism Status, and Intestinal Digestive Enzyme Activities in Meat Ducks - Junjie Jiang (Animals, 2020)
Two experiments were conducted to investigate the effects of dietary supplementation with protease and phytase on growth performance, serum physiochemical parameters, and activities of digestive enzymes in jejunal digesta of meat ducks. Experiment 1 was carried out to determine the effects of different protease or phytase on growth performance, serum physiochemical parameter, and activities of digestive enzymes in jejunal digesta of meat ducks to select the optimal phytase or protease. According to the hatching age and initial weight, a total of 5040 Cherry Valley ducks (15 days of age) were randomly assigned into six treatments. Treatments included a basal control diet (CON) and 5 basal diets supplemented with different enzyme preparations, which were phytase preparation A (PA, 160 g/t), phytase preparation B (PB, 800 g/t), protease preparation A (PTA, 80 g/t), protease preparation B (PTB, 300 g/t) and protease preparation C (PTC, 200 g/t). The enzyme activities were as follows: Phytase A and B as well as protease A, B, and C were 50,000, 10,000, 250,000, 50,000, and 60,000 U/g, respectively. Each treatment had 7 replicates with 120 meat ducks per replicate. Experiment 1 lasted for 28 days. The results showed that: compared with the CON group, the PA group significantly decreased contents of serum phosphorus and calcium (p < 0.05), and the PTA, PTB, and PTC groups had higher activities of trypsin in jejunal digesta (p < 0.05), and the activity of jejunal chymotrypsin in PTA group was greater (p < 0.05). Experiment 2 was carried out to determine the effects of dietary supplementation with protease and phytase in low-energy and low-protein diet on growth performance, serum physiochemical parameters, and activities of digestive enzymes in jejunal digesta of meat ducks. According to the hatching age and initial weight, a total of 5760 Cherry Valley ducks (15 days of age) were randomly assigned into four treatments on the basis of a trial of 2 × 2 factorial design. Treatments included a basal control diet (PC), basal diet supplemented with enzymes (PCE), low-energy and low-protein diet (LEP), and low-energy and low-protein diet supplemented with enzymes (LEPE), the nutrient levels of energy and CP of basal diet were 2747.2 cal·ME/kg and 16.80%, respectively, and the nutrient levels of energy and CP of low-energy and low-protein diet decreased 45.90 kcal·ME/kg and 0.52% on the basis of basal diet, respectively. According to the results of experiment 1, phytase A and protease A were determined as the optimal enzyme combination of Experiment 2, and additional dosage of which were identical with Experiment 1. Each treatment had 6 replicates with 240 meat ducks per replicate. Experiment 2 lasted for 28 days. The results showed that: compared with PC and LEP groups, PCE and LEPE groups had higher final weight and average daily gain (ADG) (p < 0.05), higher activities of trypsin and chymotrypsin in jejunal digesta (p < 0.05), lower contents of serum calcium and phosphorus as well as higher levels of high-density lipoprotein in the serum (p < 0.05). In conclusion, dietary supplementation with phytase and protease in different energy and protein diets could increase digestive enzymes in jejunal digesta, effect serum physiochemical parameters, improve metabolic status, and increase the growth performance of meat ducks. Meanwhile, with the dietary supplementation with phytase and protease in the lower energy and protein diet, the growth performance could reach to the degree of the higher energy and increased protein diet, but without the addition of phytase and protease.